(untitled) (Вестник КазНУ. Серия Экономическая, 2022)
The article is devoted to the development of an algorithm for evaluating the effectiveness of modeling the company’s business processes in the context of digitalization. The algorithm for evaluating the effectiveness of modeling a business process proposed in this work presents a list of actions and works to obtain the necessary effect – increasing the efficiency of modeling business processes (main and auxiliary) in the context of digitalization. The calculation of indicators of efficiency of modeling business processes for enterprises in the service sector is given. Mainly organizations in the service sector consider business processes in the context of four separate categories: – development of products and services; – demand generation; – satisfaction of demand; – planning and enterprise management. Efficiency evaluation can be carried out at the planning stage of digital transformation activities and at the final stage, when digital technologies are introduced at a certain stage of the product life cycle or any stage of the digital transformation and robotization strategy is implemented. The algorithm proposed by the authors for assessing the effectiveness of modeling the business processes of a company in the context of digitalization makes it possible to determine the feasibility of digitalization of companies and to take measures to introduce digital technologies. The authors note that it is necessary to calculate the effectiveness of certain changes in order to assert with confidence that the key processes in the enterprise as a result of the introduction of digital technologies will significantly improve. Key words: algorithm, efficiency evaluating, business process, digitalization, modeling, enterprises